IoT-Based Smart Plug with Real-Time Energy Measurement Optimization and Adaptive Current Cutoff (Jurnal Elektronika dan Telekomunikasi, 2025)
The use of electrical energy as a primary power source is increasing, with the residential sector being one of the largest consumers. Electrical energy expenditure often occurs accidentally, potentially leading to energy waste. This research develops an IoT-based electricity usage monitoring system to minimize electrical energy waste and help users improve efficiency and protection against voltage spikes using the R&D approach with a waterfall model.There are 3 layers of IoT architecture using the PZEM-004T sensor as a measuring device for electrical parameters and ESP8266 as a communication module where the results of the sensor readings will be displayed in real-time on the LCD and Blynk with a time difference of 1.6 seconds, in addition to the cost indicator, and the current flowing conditions are also displayed. Sensor readings are valid with values < ± 0.5% for current and voltage and < ± 1% for power readings. System monitoring tests were carried out on 10 electronic devices, and the results of the estimated electricity costs from the use of electrical energy of these electronic devices were obtained. The system is also equipped with a protection feature displayed with a warning indicator, where if the current exceeds 3.1A, the power will automatically be cut off within 15 seconds. This system provides a solution to the efficiency of electrical energy expenditure and provides more protection.